PEMBERDAYAAN IDENTITAS SEKOLAH MELALUI PRODUKSI VIDEO PROFIL - Putu Desi Anggerina Hikmaharyanti; Putu Gede Budiartha; Ni Nyoman Deni Ariyaningsih; I Gusti Ayu Agung Sintha Satwika; Ni Putu Cahyani Putri Utami; Yohana Maya Sari (Fakultas Bahasa Asing, 2025)
This community engagement initiative aims to strengthen the institutional identity of SD Negeri 2 Jehem, Bangli, through the production of a school profile video based on local narratives and community participation. A team from the Faculty of Foreign Languages, Universitas Mahasaraswati Denpasar, carried out a series of activities including observation, scriptwriting, and video production. The results indicate that a collaborative approach rooted in local cultural values can enhance stakeholders’ sense of ownership and pride, while also expanding the school’s visibility through digital media. This article reflects the potential synergy between academia and primary education communities in building authentic and inspiring school representations.